Constitutional Reform and the Opportunity for Higher Education Access in Ecuador Since 1950 - David Post (Education Policy Analysis Archives, 2011)
Ecuador's 2008 Constitution, and its 2009 national development plan, assign universities the role of reducing social inequality by, among other means, eliminating user fees. This article offers the first over-time assessment of the background tendencies in the accessibility to secondary and postsecondary university. Based on the analysis of 1990 and 2001 census data, and on household surveys from 1988 to the present, I find that women have overtaken men in all levels of education participation. The gaps are growing between ethnic groups, income groups, and language groups. This historic tendency will be difficult to reverse through the suspension of user fees because the main beneficiaries of free higher education are the most advantaged students in Ecuador.